Hawking radiation as stimulated emission - Wen-Yu Wen (Physics Letters B, 2020)
We regard the Parikh-Wilczek's tunnelling model of Hawking radiation as a quantum mechanical process of stimulated emission. The hypothesized microstates are found seated at the horizon with double degeneracy. A Jaynes-Cummings toy model for a black hole in the cavity is proposed to demonstrate how to write a qubit via the angular-dependent transition coupling, which might be related to the soft Goldstone hairs after analytic continuation. At last, we show how information is retained in the black hole by computing the time evolution of mutual entanglement entropy in the cavity-black holes system. Keywords: Hawking radiation, Jaynes-Cummings model, Stimulated emission